1984
DOI: 10.1007/bf00228424
|View full text |Cite
|
Sign up to set email alerts
|

Organization and morphogenesis of the human seminiferous epithelium

Abstract: The various types of human primary spermatocytes were classified by means of morphological and morphometrical studies. Based on this classification, the topographic arrangement of the spermatocyte populations in the longitudinal course of seminiferous tubules was determined. This analysis revealed human spermatogenesis be to subjected to a complex local plan of organization, which is based upon the geometry of spirals. The centers of gravity of spermatocyte populations of subsequent degrees of differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(44 citation statements)
references
References 29 publications
4
40
0
Order By: Relevance
“…In addition to the rat, in which the wave has been most vividly illustrated (Perey et al, 19611, the wave has been reported to occur in the mouse, bull, guinea pig, rabbit, ram, boar, dog, cat (Benda, 1887;Curtis, 19181, marsupials (Furst, 18871, and humans (Schulze, 1982;Schulze and Rehder, 1984). The current paper extends these studies by revealing the spermatogenic wave in the horse.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to the rat, in which the wave has been most vividly illustrated (Perey et al, 19611, the wave has been reported to occur in the mouse, bull, guinea pig, rabbit, ram, boar, dog, cat (Benda, 1887;Curtis, 19181, marsupials (Furst, 18871, and humans (Schulze, 1982;Schulze and Rehder, 1984). The current paper extends these studies by revealing the spermatogenic wave in the horse.…”
Section: Discussionsupporting
confidence: 62%
“…Six biopsy specimens of patients with oligozoospermia constituted the control group, for they met all the following criteria of normality [15]: (1) diameter of the seminiferous tubules ranging between 180 pm and 250 pm; (2) average thickness of the lamina propria less than 10 pm; (3) presence of germ cells; (4) regular development of spermatids; (5) typical morphology of the Sertoli cells; and (6) appearance of residual bodies and spermiation. Control patients were 22-30 years old (mean 27 years).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological distinction between the various types of human spermatocytes is achieved via recognition of their position within the seminiferous epithelium, the arrangements of chromatin within the nucleus, and the size of the cells (de Kretser and Kerr, 1988;Dym, 1977;Holstein and Roosen-Runge, 1981; Schulze and Rehder, 1984;Solari and Tres, 1967;Wettstein and Sotelo, 1967). The preleptotene primary spermatocytes arise from the B-type spermatogonia, lose contact with the basement membrane, and engage in active DNA synthesis.…”
Section: The Seminiferous Tubulementioning
confidence: 99%